Military Position Transition In Every Era Of Indonesian Head Of State Leadership - Muhammad Budiana; Yusa Djuyandi (Journal of Governance, 2022)
The position of the military in taking on a political role in Indonesia has changed along with the changing leadership of the state. The dynamics of this change were born because of the pattern of civil-military relations in Indonesia. This civil-military relationship can be created when a concept called "civilian control" occurs. In this paper, we use the theory of civil-military relations according to Samuel Hantington, which is then used to analyze the involvement of the military in supporting Indonesian political decisions (Huntington, 2000). In this study, we used qualitative research methods.